Effects of ozonation on disinfection and microbial activity in waste activated sludge for land application - Ahn, KH; Maeng, SK; Hong, JS; Lim, BR (WASTEWATER SLUDGE AS A RESOURCE, 2003)
Effects of ozonation on microbial biomass activity and community structure in waste activated sludges from various treatment plants were investigated. The densities of viable cells and microbial community structure in the sludges treated with ozone at 0.1, 0.2 and 0.4 gO(3)/gDS were measured on the basis of the respiratory quinone profile and LIVE/DEAD(R) Baclight(TM). The results from the bacterial concentration and quinone profiles of the waste activated sludge showed that respiratory activities of microorganisms were detected at the ozone dose of 0.4 gO(3)/gDS. However, fecal coliform, fecal streptococcus and Salmonella sp. in the ozonized sludge were not detected. This result implies that some microorganisms might be more tolerant to ozonation than the pathogenic indicators. The pathogens reduction requirements for class A biosolids were still met by the ozonation at 0.4 gO(3)/gDS.